2004
DOI: 10.1002/bjs.4387
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of lightweight composite mesh for Lichtenstein inguinal hernia repair

Abstract: Lightweight polypropylene mesh may be preferable for Lichtenstein repair of inguinal hernia. Larger cohorts with longer follow-up are needed before it can be recommended for routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
125
3
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 12 publications
13
125
3
6
Order By: Relevance
“…The incidence of perioperarive and postoperative complications is minimal. 8 Most of the patients return to routine life within 48 hours and 60% of physical laborers return to work within 4 weeks. Yet there is a high incidence of chronic groin pain following hernia repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of perioperarive and postoperative complications is minimal. 8 Most of the patients return to routine life within 48 hours and 60% of physical laborers return to work within 4 weeks. Yet there is a high incidence of chronic groin pain following hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…7 Lichtenstein technique has since become the most commonly performed surgery for inguinal hernia and because it provides a tension-free repair with good long-term results. 8,9 Tension-free mesh repair is nevertheless associated with complications such as foreign body reaction, infection, pain, fistula formation, migration, shrinkage, and recurrence. 10 Other complications include skin anaesthesia, bruising and haematoma formation, seroma formation, orchitis and testicular atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the structure of the mesh is an important factor in the development of postoperative pain, and use of synthetic non-absorbable flat mesh or composite mesh is recommended because these cause less pain (11). Post et al (13) reported that the pain might be caused by the weight and composition of the mesh, and that the feeling of a foreign body sensation was higher in the heavyweight mesh group. In contrast, Bringman et al (14) found no difference in postoperative pain between lightweight and heavyweight mesh groups.…”
Section: Resultsmentioning
confidence: 99%
“…[4]Lichtenstein presented his open mesh repair technique for inguinal hernia in 1986. [56]Tension-free mesh repair is nevertheless associated with complications such as foreign body reaction, infection, pain, fistula formation, migration, shrinkage, and recurrence. [7]…”
mentioning
confidence: 99%
“…[20]It is now believed that most of these symptoms are related to the type of material used as mesh for the repair rather than the technique employed. [21]In the past decade, with the introduction of mesh repair for groin hernia the incidence of recurrence following the procedure was found lower than 3% in most studies. [22]…”
mentioning
confidence: 99%